Nonlinear models of transients of nuclear power steam turbines to optimize control processes - Severin, Valeriy Petrovich; Nikulina, Elena Nikolaevna; Chechenova, Irina Husenovna (Вісник Національного технічного університету «ХПІ». Серія: Енергетичнi та теплотехнiчнi процеси й устаткування, 2016)
Presentation of nonlinear models of nuclear steam turbines in the state space of relative variables to optimize the turbine control system is the aim of the article. Using the known physics laws equations describing the dynamics of NPP steam turbine as an automation object in variable modes are considered.As an example, by transforming the equations of the dynamics nonlinear model of the steam turbine K-220-4.4-3 in relative state variables is built as a system of differential equations in the Cauchy form. The model takes into account the experimental data of regulators and uses a minimal amount of computations. Graphs of nonlinear functions of flow coefficients of the variables of servomotors coordinate values of the control valve and control flap, derived from a spline interpolation of the experimental data, are constructed. Formulas for the calculation and the calculated values of the constants parameters of the model are given. The input variables of the model are the coordinates of the servomotors of control valve and control flaps, as well as the power of the electric generator. On the basis of the turbine model for the study of the load shedding mode of electric generator graphs of pressure variables in steam volumes and speed of the rotor are constructed by numerical integration of the differential equations system for given functions of closing of servomotors of control valve and control flap. The maximum casting speed of turbine rotor is 5.28 % of the nominal frequency value.Similarly, nonlinear model of a steam turbine K-1000-60/1500-2 can be obtained. Models nuclear steam turbines in relative variables with the minimum number of calculations can be used to optimize the control system parameters of the steam turbine of nuclear power plant.